Detection of muscle wasting in patients with chronic heart failure using C‐terminal agrin fragment: results from the Studies Investigating Co‐morbidities Aggravating Heart Failure (SICA‐HF). (9th October 2015) - Steinbeck, Lisa; Ebner, Nicole; Valentova, Miroslava; Bekfani, Tarek; Elsner, Sebastian; Dahinden, Pius; Hettwer, Stefan; Scherbakov, Nadja; Schefold, Jörg C.; Sandek, Anja; Springer, Jochen; Doehner, Wolfram; et al.
Abstract : Aims: Skeletal muscle wasting affects 20% of patients with chronic heart failure and has serious implications for their activities of daily living. Assessment of muscle wasting is technically challenging. C ‐terminal agrin‐fragment (CAF), a breakdown product of the synaptically located protein agrin, has shown early promise as biomarker of muscle wasting. We sought to investigate the diagnostic properties of CAF in muscle wasting among patients with heart failure. Methods and results: We assessed serum CAF levels in 196 patients who participated in the Studies Investigating Co‐morbidities Aggravating Heart Failure (SICA‐HF). Muscle wasting was identified using dual‐energy X‐ray absorptiometry (DEXA) in 38 patients (19.4%). Patients with muscle wasting demonstrated higher CAF values than those without (125.1 ± 59.5 pmol/L vs. 103.8 ± 42.9 pmol/L, P  = 0.01). Using receiver operating characteristics (ROC), we calculated the optimal CAF value to identify patients with muscle wasting as >87.5 pmol/L, which had a sensitivity of 78.9% and a specificity of 43.7%. The area under the ROC curve was 0.63 (95% confidence interval 0.56–0.70). Using simple regression, we found that serum CAF was associated with handgrip ( R  = − 0.17, P  = 0.03) and quadriceps strength ( R  = − 0.31, P  < 0.0001), peak oxygen consumption ( R  = − 0.5, P  < 0.0001), 6‐min walk distance ( R  = − 0.32, P  < 0.0001), and gait speed ( R  = − 0.2, P  = 0.001), as well as with parameters of kidney and liver function, iron metabolism and storage. Conclusion: CAF shows good sensitivity for the detection of skeletal muscle wasting in patients with heart failure. Its assessment may be useful to identify patients who should undergo additional testing, such as detailed body composition analysis. As no other biomarker is currently available, further investigation is warranted.